(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate, through biometrics and productivity, lettuce response to irrigation blades and saline levels under field conditions and in protected environment. The design was in randomized blocks, 5 blocks, in factorial scheme 5x5. Irrigation blades were used: (L1= 50, L2= 75, L3= 100, L4= 125 and L5= 150% ETc) and saline water levels: (S1= 0.12, S2= 1.12, S3= 2.12, S4= 3.12 and S5= 4.12 mS cm -1). The evaluated variables were: plant height (PH), capony diameter (CD), leaf area index (LAI), sheets number index (SNI), total fresh matter (TFM), total dry matter (TDM), lettuce productivity (LP) e productivity of use of water in lettuce (PUW). The data obtained were subjected to analysis of variance and regression analysis in response surface, using the statistical software R. For biometrics, the better results were observed for the PH variable in a protected environment and the CD in the field. The LAI had better results in the field and the SNI variable, in a protected environment. For LP, field cultivation obtained the best results, reaching a productivity of 13.52 t ha-1. For the variables PH, CC, LAI, SNI, TFM, TDM e LP the best results were obtained for blades equal to or greater than 100% ETc and the salinity between 0.12 and 1.12 mS cm-1. Already the variable PUW had a decreasing behavior with the increase of the irrigation depth in the two cultivation environments.